Potential Adverse Cardiovascular Effects of Treatment With Fluoxetine and Other Selective Serotonin Reuptake Inhibitors (SSRIs) in Patients With Geriatric Depression: Implications for Atherogenesis and Cerebromicrovascular Dysregulation - Ungvari, Zoltan; Tarantini, Stefano; Yabluchanskiy, Andriy; Csiszar, Anna (Frontiers in Genetics, 2019)
Late life depression is an important public health problem, which associates with increased risk of morbidity and mortality. Selective serotonin reuptake inhibitors (SSRIs), including fluoxetine, are often prescribed to treat geriatric depression. There is increasing evidence that fluoxetine and other SSRIs exert a wide range of cardiovascular side effects. Furthermore, there is evidence that aging may increase plasma level of SSRIs. In this overview, the potential role of side effects of treatment with fluoxetine and other SSRIs in the pathogenesis of age-related cardiovascular diseases, including atherogenesis, cardiac pathologies, and cerebromicrovascular impairment, is discussed.